Determinan Tax Avoidance: Bukti Empiris pada Perusahaan Publik di Indonesia - Sumartono, Sumartono; Puspasari, Indah Wahyu Tri (Jurnal Ilmiah Akuntansi, 2021)
This study aims to examine and analyze the variables that influence companies to undertake tax avoidance efforts, such as profitability, leverage, firm size, audit committee and executive character variables based on relevant empirical data. Research analysis on a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2019 that supports our hypothesis. With the number of observations observed as many as 55 companies. The results showed that three variables had a significant positive effect, namely Leverage (DAR), Audit Committee (KA), and Executive Characteristics (KE), then one other variable had a significant negative effect, namely the Profitability (ROA) variable, while the last variable did not have a significant negative effect. the effect on tax avoidance is the variable company size (SIZE) on tax avoidance. This article adds to the study of the effect ofÂ profitability, leverage, firm size, audit committee, and executive characteristics on tax avoidance and has implications for corporate management and policy makers.